Acoustic imaging of variable water layer structure in Rockall Trough, NE Atlantic - Sutton, Ciaran (Trinity College (Dublin, Ireland). Department of Geology, 2012)
A new application of an old technique to study the Earth’s interior is allowing us to see stratification in the ocean, providing a new insight into oceanic structure and mixing processes. The new adaptation of seismic reflection profiling can create detailed pictures of eddies, internal waves, and other oceanic features that affect climate, fisheries and the spread of pollution. This thesis focuses on the Rockall Trough area off the west coast of Ireland, in which reprocessed profiles show a seismically bright reflective region at depth in the sea. Structures are observed within these layers including dipping reflectors close to the slope, eddy like features and undulations within reflectors that represent internal waves. Seismic reflection sections provide very high resolution images of the oceans structure, both vertical and, in particular, horizontal, and complement conventional physical oceanography data. Seismic sections across Rockall Trough show strong lateral variability in reflectivity within the North Atlantic Central Water and Mediterranean Outflow Water (MOW) layers. As a result the reflections between adjacent or intersecting sail lines are often offset. Hence, from an oil industry perspective, there may be problems in suppressing multiples from water layer reverberations. When processing seismic surveys of regions of high oceanic variability, it is necessary to use procedures that can solve for and then remove the effect of significant fluctuations in water layer sound speed over time periods as short as a few hours and distances as short as a kilometre.
Keywords: Geology, Ph.D.; Ph.D. Trinity College Dublin